Implementation of the PAIKEMI Learning Model to Optimize Students’ Learning Achievement at MTs MBS Enrekang - Zamri, Zamri; Patintingan, Amir; Djamaluddin, Djamaluddin; Ramli, Rosmiati; Sumadin, Sumadin (Edumaspul: Jurnal Pendidikan, 2026)
This study aims to analyze the implementation of the PAIKEMI learning model (Active, Innovative, Creative, Effective, Enjoyable, and Islamic Learning) in improving students, learning achievement in Islamic Religious Education at MTs Muhammadiyah Boarding School (MBS) Enrekang Regency. The focus of the research includes the strategies used by teachers in applying the PAIKEMI model, the instructional methods employed, as well as the supporting and inhibiting factors encountered during the learning process. This research employed a descriptive qualitative approach with a case study design. Data were collected through observation, in depth interview, questionnaires, documentation, and field notes. Data analysis was conducted through data reduction, data display, and conclusion drawing to obtain a comprehensive understanding of the instructional practices. The findings indicate that the implementation of the PAIKEMI model has a positive impact on improving students learning achievement in cognitive, affective, and psychomotor domains. Students became more active, confident, and capable of critical thinking, while also showing improvement in relegious practices and Islamic character development. Various instructional methods such as discussions, question answer sessions, demonstrations, games, and group learning successfully created an interactive and enjoyable learning atmosphere. Support from the school principal, teacher competence, and the boarding school environment served as major supporting factors, whereas limited facilities and learning media remained challenges that require further optimization. The implication of this study emphasies that the PAIKEMI model is strategic alternative for Islamic Religious Education, as it enhances not only academic achievement but also students’ religious character and social skills. These findings are expected to serve as a reference for educators and educational institutions in developing innovative, contextual, and value based learning practices